Distributed Leadership Contribution towards Organizational Commitment of the NPQEL- Certified Principals in Malaysia - Md Zin, Zaharul Arifin; Hamzah , Mohd Izham Mohd; Nor, Mohamed Yusoff Mohd (International Journal of Psychosocial Rehabilitation, 2020)
Malaysian Education Blueprint 2013-2025 has outlined that high-performance leaders will be placed in every school, among others. Distributed leadership is seen as an alternative for teachers to provide opinions on school administration as it emphasizes the sharing of leadership among followers. In addition, organizational commitment is seen as an important aspect of improving organizational performance and success in an organization. This study aimed to determine the level of distributed leadership practice among NPQEL- certified principals in Malaysia. This study also aimed to identify the distributed leadership relationship among NPQEL-certified principals with their organizational commitment and the contribution of the different dimensions of distributed leadership towards principals' organizational commitment. This quantitative study used a survey method on a population of 1169 principals with 278 samples. A descriptive data analysis was performed using the IBM SPSS Statistics Version 25 and while inferential data analysis was obtained through the use of SEM SmartPLS3.0. The results showed that the level of practice of distributed leadership of NPQEL-certified principals is high and there is a positive and significant relationship between distributed leadership and organizational commitment. While, teamwork and supervisory dimensions contributed significantly to the principals’ organizational commitment.